Certain pseudo-differential operators and wavelet transforms involving fractional fourier and fractional hankel transforms - Mishra, Kush Kumar (IIT(BHU) Varanasi, 2023)
Abstract is available in the content.
Keywords: Certain pseudo-differential; operators and wavelet transforms; involving fractional fourier; and fractional hankel transforms